2015
DOI: 10.1371/journal.pone.0136451
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Dependent Inhibition of the Human Organic Cation Transporter OCT2: A Comparison of Metformin with Experimental Substrates

Abstract: The importance of the organic cation transporter OCT2 in the renal excretion of cationic drugs raises the possibility of drug-drug interactions (DDIs) in which an inhibitor (perpetrator) drug decreases OCT2-dependent renal clearance of a victim (substrate) drug. In fact, there are clinically significant interactions for drugs that are known substrates of OCT2 such as metformin. To identify drugs as inhibitors for OCT2, individual drugs or entire drug libraries have been investigated in vitro by using experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 35 publications
3
91
1
3
Order By: Relevance
“…With the information gained from these screens, plus IC 50 values determined for a structurally diverse subset of these compounds, we generated machine-learning and pharmacophore models, respectively. In contrast to the behavior observed with some other multidrug transporters (Ekins et al, 2002b;Garrigues et al, 2002;Westholm et al, 2009;Roth et al, 2011;Belzer et al, 2013;Hacker et al, 2015), the results suggest that substrate identity exerts comparatively little influence on ligand interaction with MATE1. (Aavula et al, 2006).…”
Section: Introductioncontrasting
confidence: 95%
See 2 more Smart Citations
“…With the information gained from these screens, plus IC 50 values determined for a structurally diverse subset of these compounds, we generated machine-learning and pharmacophore models, respectively. In contrast to the behavior observed with some other multidrug transporters (Ekins et al, 2002b;Garrigues et al, 2002;Westholm et al, 2009;Roth et al, 2011;Belzer et al, 2013;Hacker et al, 2015), the results suggest that substrate identity exerts comparatively little influence on ligand interaction with MATE1. (Aavula et al, 2006).…”
Section: Introductioncontrasting
confidence: 95%
“…Decision tree-based predictions of potential DDIs with multidrug transporters are complicated when the quantitative profile of inhibition of transport by a potential perpetrator is influenced by the choice of substrate used to assess transport activity (e.g., Hacker et al, 2015). Although increasingly viewed as an issue for OCTs, P-glycoprotein, and organic anion-transporting polypeptides (Garrigues et al, 2002;Roth et al, 2011;Belzer et al, 2013;Hacker et al, 2015), the extent to which ligand interaction with MATE1 displays a similar substrate dependence is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A downregulation of OCT2 was associated with an experimental acute renal failure in rats (4,5), indicating that OCT2 may play an important role in renal disease. It was recently demonstrated that OCT2 is important for renal metformin transport, and other cationic drugs may competitively inhibit the renal metformin transport (6).…”
mentioning
confidence: 99%
“…Plazemske koncentracije metformina običajno dosežejo vrednosti med 1 in 50 μM, pri čemer so višje koncentracije dokazali v portalnem sistemu in jetrih (22). Metformin se v telesu večinoma ne presnavlja in se v več kot 90 % izloča z urinom s pomočjo tubulne sekrecije preko prenašalca OCT2 v ledvicah (17,23). Zaradi nezmožnosti pasivnega prestopa v znotrajcelični prostor so terapevtski uspehi zdravila lahko odvisni od izraženosti oziroma različnih genetskih oblik membranskega prenašal-ca OCT (1/2/3) (24,25).…”
Section: Farmakokinetika Metforminaunclassified